In-season monotony, strain and acute/chronic workload of perceived exertion, global positioning system running based variables between player positions of a top elite soccer team - Oliveira, Rafael (2021)
Background: The interpretation of the load variations across a period seems important to control the weekly progression or variation of the load, or to identify within- micro and mesocycle variations. Thus, the aim of this study was to describe the in-season variations of training monotony, training strain, and acute: chronic workload ratio (ACWR) through session rating of perceived exertion (s-RPE), total distance and high-speed running (HSR) according to playing positions in an elite soccer team. Methods: Seventeen professional players from an European First League team participated in this study. They were divided four central defenders (CD), three wide defenders (WD), four central midfielders (CM), three wide midfielders (WM) and three strikers (ST). The players were monitored daily over a 41-week period of competition where 52 matches occurred during the 2015–2016 in-season. Through the collection of s-RPE, total distance and HSR, training monotony, training strain and ACWR were calculated for each measure, respectively. Data were analysed across ten mesocycles (M: 1–10). Results: The main results showed significant differences (p < 0.05) for TMs-RPE between CD vs. ST (moderate effect) in M2; between CD vs. CM (moderate effect) for TS of s-RPE; between CD vs. ST moderate effect) in M6 for ACWR of s-RPE. In addition, there was significant difference between CM vs. ST (moderate effect) in M2 for TS of TD; between WD vs. ST (moderate effect) in M3 for ACWR of TD. Moreover, there were significant differences for TM of HSR between CD vs. WD (very large effect); CD vs. WD (moderate effect) in M4 for TS of HSR. Conclusions: The present study presents new insights to coaches and technical staff about the variation profiling of TM, TS, and ACWR calculated with internal and external load measures, between player positions during 10 mesocycles.